(untitled) (Journal of Dhaka Medical College, 2024)
Background: Diabetes mellitus (DM) is a systemic disease that alters the metabolism of blood sugar. Poorly controlled diabetes or hyperglycaemia is associated with an array of micro-vascular, macro-vascular, and neuropathic complications. There is a widely held belief that infections are usually more frequent and severe in diabetic patients. Diabetes prevalence is increasing in the developed & developing countries, and the appropriate management of patients with diabetes has become increasingly important for the prevention of hospital-acquired infections. Postoperative wound infection continues to be a major source of morbidity and mortality in developing countries despite recent advances in aseptic techniques. There is little information regarding postoperative wound infection in controlled diabetic patients undergoing elective operation. Objectives: The aim of our study was to evaluate the postoperative wound infection in controlled diabetic and non-diabetic patients in elective operations. Materials & method: This cross sectional comparative study was conducted in Department of Surgery, Bangabandhu Sheikh Mujib Medical University, Dhaka, during the period of October 2011 to March 2012. A total seventy three patients with controlled diabetics and seventy three non-diabetics were selected. Inclusion criteria were patients undergoing clean and cleancontaminated elective operations. Un-controlled diabetes, patient undergoing contaminated and dirty operation, patient with tuberculosis, jaundice, uraemia, having cortico-steroids /chemoradiation and operated for malignancies were excluded. After preoperative preparation specific operation was done. All patients were followed up for 30 days of post operative period for development of any postoperative wound infection. All information recorded in data collection sheet. Data was processed and analysed with the help of computer program SPSS-16 and Microsoft excel. Quantitative data expressed as mean and standard deviation and qualitative data as frequency and percentage. Result: The patients of diabetic group [31 male, 42 female; mean age, 44.5 (SD 8.2) years] and non-diabetic group [40 male, 33 female; mean age, 43.1 (SD 9.4) years] were similar in age and sex (p>0.05 each). The rate of postoperative wound infection after elective abdominal surgery was 7.5% [in controlled diabetic group was 12.3% and that of non-diabetic group was 2.7% (p<0.05)] and the patients of diabetic group were 5.0 times more likely to develop wound infection as compared to that of non-diabetic group (OR=4.992; 95% of CI=1.040–23.971) in clean and clean contaminated elective abdominal surgery. The length of postoperative hospital stay was significantly more in diabetic group than that of non-diabetic group (8.2 (SD ± 2.9) vs 6.8 (SD ± 3.2) days; p<0.01). Conclusion: Postoperative wound infection was higher in controlled diabetic patients than that of non-diabetic. These results support the consideration of diabetes as an independent risk factor for SSIs after elective surgery. Continued efforts are needed to improve surgical outcomes for diabetic patients. J Dhaka Med Coll. 2022; 31(2) : 226-231